Husband’s involvement with mother’s awareness and knowledge of newborn danger signs in facility-based childbirth settings: A cross-sectional study from rural Bangladesh - Zaman, Sojib Bin; Gupta, Rajat Das; Al Kibria, Gulam Muhammed; Hossain, Naznin; Bulbul, Md. Mofijul Islam; Hoque, Dewan Md Emdadul (BMC, 2022)
This article was published in the BMC Research Notes [© The Author(s) 2018. This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1186/s13104-018-3386-6 The Journal's website is at: https://bmcresnotes.biomedcentral.com/articles/10.1186/s13104-018-3386-6#citeas